Sie sind auf Seite 1von 31

 

 

 

 

 

 

 

 

 

 

 

 

 

 

 

 

 

 

 

 

 

 

µ

p

 

 

µ

p

X

x 1 ,

x (1) x (2)

, x n n

x (n)

X x 1 ,

n

x i n(X = x i ) n i

, x k k

x i h(X = x i ) = h i = n i /n

i

h(X x i ) = j=1 h j x 1 < x 2 < ··· < x k

ˆ

F(x i )

         

i

ˆ

i

x

i

n

i

h

i

j=1 h j =

F(x i )

 

 

 

k n

h(X x) x

x 1 < x 2 <

< x k

ˆ

F(x) = h(X x) =

0

i j=1 h j

1

x < x 1

x i x < x i+1 ,

i = 1,

x x k

, k 1

X k

(x 0 , x ], (x , x 2 ], (x 2 , x 3 ],

1

1

, (x

k1 , x

k ].

i (x

]

n i n(x i1 < X x )

i1 , x i

i

n

i h i = n i /n h(X x ) = j=1 h j

i

i

f h i

i = x

ˆ

i x i1

  h(x i1 < X x

 

i )/i

x i1 < x x

i

 

i

= 1,

, k

 
 

ˆ

f(x) =

,

 

0

 

i

x i1 < X x

 

h

   

ˆ

i f(x)

   

i

j=1 h j =

ˆ

F(x

)

i

 

n

i

i

i

   

 

       

 

 

 

 

ˆ

f

x

h i i

ˆ

F(x) = h(X x) =

0

i1

j=1 h j + (x x

1

i1 ) ·

ˆ

f(x

i

)

x x

0

x i1 < x x

x > x

k

i

,

i = 1,

, k

ˆ

x

i

, i = 1,

, k F(x )

i

j=1 i h j

ˆ

ˆ

F(x) = F(x i1 ) + (x x

i1 ) ·

ˆ

f(x

i

) x i1 < x x

i

, i = 1,

, k.

x

x = 1

n

n

i=1

x

i

x

k

i=1

m i · h i

,

m i i m i = x

i1 + x i

2

z i = x i + y i ,

y i = a + b x i , i = 1,

i = 1,

, n :

, n :

y = a + b x

z = x + y

x 0.50

, x (n) n

x (1) ,

n

x 0.5 =

x ((n+1)/2)


(x (n/2)

1

2

+ x (n/2+1) )

n

n

x

d 2

x

d 2

d 2 = 1

n

n

i=1

(x i x) 2

d 2

k

i=1

(m i x) 2 · h i

m i i

d 2 = x 2 x 2 ,

x 2 x 2 =

y i = a + b x i

1

n i=1 n x i

2

d y = b 2 d

2

2

x

x 0.25

x 0.75

n

x 0.25

x 0.75

p 0 < p 1

ˆ

ˆ

F(x i1 ) < p F(x

i ) p

x p = x

ˆ

i1 + p

F(x

i1 )

ˆ .

f(x

i )

IQR = x 0.75 x 0